Multimodal Neuroanesthesia with an Ultrasound-Guided Dexamethasone-Adjuvanted Scalp Block for Endoscopic Transsphenoidal Resection of a Giant Sellar-Suprasellar Rathke Cleft Cyst: A Case Report - Angga Andre Fahrizal; Buyung Hartiyo Laksono; Dewi Arum Sawitri (Journal of Anesthesiology and Clinical Research, 2026)
Introduction: Sellar and suprasellar masses commonly present with visual failure and endocrinopathy, and the endoscopic endonasal transsphenoidal route is now the standard corridor for their resection. The procedure imposes intense but intermittent nociceptive surges upon a narrow, blood-intolerant surgical field, so the neuroanesthetic plan must reconcile profound analgesia, brain relaxation, hemodynamic stability, and rapid neurological emergence. We describe the perioperative management of a giant Rathke cleft cyst using a multimodal regimen anchored by a regional scalp block. Case Presentation: A 45-year-old woman (body mass index 31.1 kg/m²) presented with one year of progressive bitemporal visual field narrowing. Magnetic resonance imaging showed a cystic sellar-suprasellar mass with a mural nodule compressing the optic chiasm, favoring a giant Rathke cleft cyst over a sellar abscess. She was American Society of Anesthesiologists physical status III with stage 1 hypertension. Under total intravenous anesthesia titrated to a bispectral index of 40 to 60, a bilateral scalp block using 0.375% ropivacaine with 10 mg dexamethasone in 20 mL was performed after induction to blunt the sympathetic response. Mean arterial pressure was held at 65 to 80 mmHg across the five-hour endoscopic transnasal resection with sphenoidectomy and nasoseptal flap reconstruction. Emergence was smooth without bucking. In intensive care the patient was Glasgow Coma Scale 15 with no deficit; urine output reached 2.35 mL/kg/hr and sodium fell mildly to 132 mEq/L, and both were managed conservatively without desmopressin. Conclusion: Integrating a fully endoscopic transsphenoidal approach with a dexamethasone-adjuvanted scalp block and target-controlled total intravenous anesthesia delivered a bloodless field, immaculate hemodynamic control, and prompt neurological recovery. Structured intensive care surveillance for diabetes insipidus and dysnatremia secured a safe trajectory, offering a transferable framework for complex sellar tumor anesthesia.